Telaprevir or boceprevir triple therapy in patients with chronic hepatitis C and varying severity of cirrhosis. Issue 10 (24th March 2014) - Saxena, V.; Manos, M. M.; Yee, H. S.; Catalli, L.; Wayne, E.; Murphy, R. C.; Shvachko, V. A.; Pauly, M. P.; Chua, J.; Monto, A.; Terrault, N. A.
Summary Background Risks and benefits of protease inhibitor (PI) (telaprevir or boceprevir) triple therapy in hepatitis C virus (HCV)‐infected patients with mildly decompensated cirrhosis, including those wait‐listed for liver transplantation (LT), are incompletely known. Aim To assess virological responses and safety of PI triple therapy in patients with mildly decompensated Child‐Pugh (CP) CP ≥6 vs. compensated (CP = 5) cirrhosis. Methods Multicentre cohort of 160 adults with cirrhosis treated with peginterferon/ribavirin (peg‐IFN/RBV) plus telaprevir (69%) or boceprevir (31%), comparing outcomes between those with CP = 5 and CP ≥6. Results Patients, 47% with CP ≥6 cirrhosis (CP range 6–10), received PI triple therapy for a targeted duration of 48 weeks. The cohort was median age 59 years, 32% female, 59% genotype 1a, 35% previous null/partial responders. Sustained virological response at 12 weeks (SVR12) was achieved by 35% of patients with CP ≥6 vs. 54% of those with CP = 5 (P = 0.02). CP = 5, achievement of rapid virological response and genotype 1b/other, independently predicted SVR12. Compared to those with CP = 5, patients with CP ≥6 had more peg‐IFN dose reductions, eltrombopag use, transfusions and hospitalisations to manage adverse events (all P < 0.05). Overall, 67 (42%) discontinued treatment early. Nine wait‐listed patients were treated for a median of 97 days (IQR 60–160) prior to liver transplantation and five achieved post‐LT SVR. Conclusions In the presence of mild decompensation (Child‐Pugh ≥6), SVR12 rates with protease inhibitor triple therapy are significantly reduced and adverse events increased. Thus, treatment with protease inhibitor triple therapy, if judged as necessary, should be undertaken with close monitoring and awareness of the significant risks.